Vesta and the HED meteorites: Mid‐infrared modeling of minerals and their abundances - Hanna, K; Sprague, A (Wiley, 2010)
We demonstrate that the use of an established spectral deconvolution algorithm with mid‐infrared spectral libraries of mineral separates of varying grain sizes is capable of identifying the known mineral compositions and abundances of a selection of howardite, eucrite, and diogenite (HED) meteorite samples. In addition, we apply the same technique to mid‐infrared spectral emissivity measurements of Vesta that have been obtained from Cornell's Mid‐Infrared Asteroid Spectroscopy (MIDAS) Survey and the Infrared Space Observatory (ISO). Each Vesta measurement was made over a different range of longitudes. Our spectral deconvolution results to the Vesta spectra corroborate that Vesta's surface is howardite or eucrite‐like in composition and heterogeneous across its surface. The spectral fits produced by the linear deconvolution algorithm yields good results for the HED samples of known composition, thus giving us a high degree of confidence that our results for Vesta are valid.